2014
DOI: 10.4103/2153-3539.137726
|View full text |Cite
|
Sign up to set email alerts
|

Automated grading of renal cell carcinoma using whole slide imaging

Abstract: Introduction:Recent technology developments have demonstrated the benefit of using whole slide imaging (WSI) in computer-aided diagnosis. In this paper, we explore the feasibility of using automatic WSI analysis to assist grading of clear cell renal cell carcinoma (RCC), which is a manual task traditionally performed by pathologists.Materials and Methods:Automatic WSI analysis was applied to 39 hematoxylin and eosin-stained digitized slides of clear cell RCC with varying grades. Kernel regression was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 41 publications
0
17
1
1
Order By: Relevance
“…To the best of our knowledge, this is the first computational pathology system created to predict 2-tiered ccRCC grade with prognostic significance. Previously, Yeh and colleagues developed an automated system to predict grade using a dataset of 39 patients and one feature (i.e., maximum nuclei size), and correlated their predicted grade with manual grade assessed by one pathologist 28 . Our system, trained using a much larger and more diverse dataset of 277 cases from seven TCGA participating institutions, captures 72 nuclei details in addition to morphological features (i.e., nuclei size and shape) typically observed by pathologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first computational pathology system created to predict 2-tiered ccRCC grade with prognostic significance. Previously, Yeh and colleagues developed an automated system to predict grade using a dataset of 39 patients and one feature (i.e., maximum nuclei size), and correlated their predicted grade with manual grade assessed by one pathologist 28 . Our system, trained using a much larger and more diverse dataset of 277 cases from seven TCGA participating institutions, captures 72 nuclei details in addition to morphological features (i.e., nuclei size and shape) typically observed by pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…While qualitative evaluation of the segmentation results revealed that our image processing pipeline produced reasonably good results, the nuclei segmentation may not be optimal in more challenging cases. A solution is to employ deep learning based techniques to improve nuclei segmentation in future studies 28,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Selection and grading of the field-of-interest can be subjective and biased. The WSI method that we have developed provides an overall and quantitative evaluation of the whole pathology slide without pre-selecting field-of-interest [28]. The computational detection algorithm provides an objective and quantitative evaluation of the true pathological evaluation of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The whole-slide images were then processed by WS-Recognizer (http://ws-recognizer.labsolver.org) [28]. The cell nuclei in the H&E-stained slides were recognized to calculate the cell density across the entire tissue section, whereas the ED1 + macrophages were recognized to calculate the spatial distribution of macrophages.…”
Section: Pathological Analysis and Whole-slide Imaging (Wsi)mentioning
confidence: 99%
“…Aplikacje te korzystają zarówno z WSI, jak i narzędzi do automatycznej analizy obrazu. Zastosowanie CAD może obejmować między innymi stopniowanie histologiczne nowotworów (grading) i kwalifikację chorych do terapii [44]. Ponadto pozwala ono na automatyczne wybieranie obszarów do analizy w celu oceny tak zwanych hot spotów, czyli obszarów nowotworów o najwyższej aktywności proliferacyjnej [45].…”
Section: Diagnostyka Cyfrowaunclassified